The techniques of judo - Takagaki, Shinzo; Sharp, Harold E.
The techniques of judo is a fully illustrated and authoritative manual giving step-by-step explanations, practical pointers, and through analyses of all the most commonly used techniques or wazas of judo. Illustrated with over 550 black-and-white photographs. This book is an invaluable introduction for the beginner as well as a complete repertory for the advanced judoka. incisive description of more than 70 hand throws, hip throws, leg throws, back and side throws, holding techniques, strangling techniques, armlock techniques, together with their variations and appropriate counter-techniques are included herein.